The Impact of Diversity of Human Resources to achieve Strategic Flexibility in the Jordanian Islamic Bank - Khasawneh, Maen Yousef; Zawaedih, Mohammed Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
The main objective of this study was to identify the impact of Diversity of Human Resources on Strategic Flexibility of the Jordanian Islamic Bank. The study included two variables: Diversity of Human Resources in all its dimensions (gender, age, educational, experenance) as an independent variable and strategic flexibility in all its dimensions (Market Flexibility, Human Resources Flexibility, Production Flexibility) as a dependent variable. The study assumed that there is no relationship between Diversity of Human Resources and strategic flexibility, in order to achieve the objectives of the study, the researcher relied in preparing his study on the descriptive- analytical approach, in addition to using the questionnaire as a main tool and method for data collection. With the use of SPSS V23 statistical software for data analysis. the researcher chose a simple random sample of 335 employees. Through analyzing the data, the researcher reached several important results, the most prominent of which are: There is a significant relationship between the role of Diversity of Human Resources on Strategic Flexibility in all its dimensions (Market Flexibility, Human Resources Flexibility, Production Flexibility) In the Jordanian Islamic Bank, the overall average answers for the workers on Diversity of Human Resources comes medium, with an arithmetic average (3.60), while Strategic Flexibility was come high with an arithmetic average (3.72). Based on the findings of the study, the Study recommends several recommendations, the most important of which are: should be continue practicing the strategic flexibility in the Jordanian Islamic Bank, in a way that makes it able to accommodate the environmental changes and the market, then dealing with them.
Keywords: diversity of human resources; strategic flexibility; Jordan Islamic Bank